Al-Mar’ah fī Syi’ri al-Hubbi bila Hudūdi (al-Ẓawāhir al-Hirmulūjiyyati) - Khafid Roziki (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This study aims to determine the meaning of the concept in the poem Al-Hubb Bilậ Hudậd by Nizar Qabbani. This study uses Paul Ricoeur's hermeneutic analysis in interpreting symbols and meanings that are still veiled in the Al-Hubb Bilậ Hudṻd poem which consists of deciphering the hidden meaning behind the visible meaning, and at the level of meaning implicit in the literary meaning. Data analysis was carried out using various data collection techniques (triangulation), and carried out continuously. The analysis technique used in this research is to understand the meaning of poetry, identify the semantic meaning, describe the existential/ontological meaning, by decontructuring and reconstructing the text. The results of this study using Paul Ricoeur hermeneutics analysis there are two concepts, namely structural and phenomenal interpretation. In structural interpretation, women are metaphors of natural beauty metaphors, and men are loyal lovers. And in a phenomenal interpretation, a woman is a woman who has a smooth, gentle character, full of coolness and sincere affection of all time, so that she can grow a good generation. A man's love for women should never be interrupted and in fact must always give more to all roles and struggles of women in a family.